Model Pembelajaran Flipped-Guided Inquiry Learning (Fgil) Untuk Pembelajaran digital Bagi Mahasiswa Kimia Tahun Pertama. - Mawardi Mawardi; Muhammad Iqbal Nur (Postgraduate, University of Mataram, 2022)
The COVID-19 pandemic that has hit Indonesia has changed the learning process at every level of education including in universities, face-to-face learning that was previously carried out has turned into online learning, this is also what causes digital learning at this time to become a necessity. Flipped Learning Model - Guided Inquiry Learning (FGIL) is one of the learning models that can be applied to digital learning models. The type of research used is the educational design reservoir (EDR) which was developed using the plomp model. The subjects of this study consisted of lecturers from Padang State University and students studying general chemistry. The instrument used consists of a validity questionnaire, a practicality questionnaire. Validity data was obtained using Aiken's V formula and practicality data was obtained using the practicality percentage formula. Based on the research conducted, the media validation and content validity values were obtained respectively, while the practicality values obtained were, these results indicate that the FGIL model is valid and practical to use in the learning process